Penafsiran Ayat-Ayat Toleransi Dalam Tafsir Al-Azhar dan Al-Misbah Serta Implementasinya Terhadap Masyarakat Indonesia - Faliech Saiful Khawash; Muslihudin; Abid Nurhuda; Anas Assajad; Dewi Sinta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
There must be no spelling, grammatical or expression errors in the language used. Indonesia is a plural country, but most people still do not realize and understand the concept of tolerance which results in harmony. The proof is that there are still conflicts between religions such as in East Java in December 2021, in Brikang Village, Menganti sub-district, Gersik, Central Java on April 10, 2022, even 50% of utterances on social media contain intolerant values. This arises because of the lack of understanding of the Muslim community, especially of the content of the Qur'an about the importance of tolerance. The purpose of this research is to examine how the content of tolerance verses in Al-Azhar and Al-Misbah commentaries, is then contextualized in the life of Indonesian society. This research method uses a qualitative method of thematic literature study. The results of this study indicate that Hamka and Quraisy Shihab in Qs. Al-An'am verse 108, QS. Al-Mumtahanah verse 8-9, QS. Saba's verse 25 states that insulting, reviling, and discriminating against non-Muslims is despicable behavior. Both of them allow associating with non-Muslims with the rules: not to criticize their beliefs, not to discuss the shortcomings of beliefs in front of them directly, associate with polite language, questions that are not offensive, associate if it provides inter-religious benefits, and does not bring madharat. However, it is still with the limitations that can be associated as long as they are not hostile and do not expel from the homeland.